Risk factors for poor sleep quality in patients with inflammatory bowel disease in China: A multicenter study - Zeng, Suqi; Liu, Chuan; Zhang, Jixiang; An, Ping; Liu, Zhongchun; Jiang, Changqing; Shi, Jie; Wu, Kaichun; Dong, Weiguo (Frontiers in Psychiatry, 2023)
Objectives: This study aimed to determine the prevalence and risk factors for poor sleep quality in inflammatory bowel disease (IBD) patients. Methods: 2478 IBD patients were enrolled to investigate their sleep quality using the Pittsburgh sleep quality index (PSQI). Clinical and psychological characteristics were collected to explore the risk factors for poor sleep quality. A hurdle model was conducted to predict poor sleep quality based on the risk factors. Among this hurdle model, the logistic regression model was used to determine risk factors of the presence of poor sleep quality, and the zero-inflated negative binomial model was employed to identify risk factors of the severity of poor sleep quality. Results: In this study, 1491 (60.17%) IBD patients had poor sleep quality, and the proportion in the older group was higher than younger group (64.89% vs. 58.27%, p = 0.003). According to multivariable logistic regression, age (OR, 1.011; 95% CI [1.002,1.020]; p = 0.014), Patient Health Questionnaire-9 (PHQ-9) score (OR, 1.263; 95% CI [1.228,1.300]; p < 0.001), systemic (OR, 0.906; 95% CI [0.867,0.946]; p < 0.001) and emotional performance (OR, 1.023; 95% CI [1.005,1.043]; p = 0.015) were risk factors of the presence of poor sleep quality. The area under the curve (AUC) of the prediction model was 0.808. According to zero-truncated negative binomial regression, age (RR, 1.004; 95% CI [1.002,1.005]; p < 0.001) and PHQ-9 score (RR, 1.027; 95% CI [1.021,1.032]; p < 0.001) were risk factors of the severity of poor sleep quality. Conclusion: The prevalence of poor sleep quality among the older group in IBD patients was relatively high. Old age and depressive mood are risk factors for both the presence and severity of poor sleep quality.